14 Effects of cardiovascular disease on the arterial pathlength between the carotid and femoral arteries. (18th May 2017) - Summersgill, Jennifer A; Weir-McCall, Jonathan R; Khan, Faisel; Colhoun, Helen M; Struthers, Allan D; Belch, Jill JF; Houston, JGraeme
Abstract : Introduction: Carotid-femoral pulse wave velocity (cf-PWV) is the gold standard of measuring PWV. The aorta becomes tortuous with ageing however reports of this impact on pathlength travelled by the pulsewave are conflicting. Additionally the effects of atherosclerotic cardiovascular disease on arterial remodelling is unknown. This study looks into age-associated changes in the arterial pathlengths amongst healthy volunteers and examines whether pathlength is altered by cardiovascular disease. Methods: To determine the effects of cardiovascular disease, 66 volunteers with known cardiovascular disease (CVD) (Age: 64.4±7.7 yrs, Female=16(17%)) were compared to 66 healthy volunteers (OHV) who were age, sex and height matched (Age: 64.6±7.2 yrs). To determine the effects of age, these were compared with 66 younger healthy volunteers (YHV) who were also sex and height matched (Age: 43.1±2.5 years). Whole body MR angiographies were performed. Curved MPRs were generated from the carotid-femoral arteries allowing true intra-arterial pathlengths to be measured. Results: Older healthy volunteers showed significantly increased intra-arterial distances compared with younger healthy volunteers (Right subtraction: YHV=431.6±50.1 mm, OHV=454.5±33 mm, p=0.005; Left subtraction:YHV=423.0±48.3 mm, OHV=449.6±34.9 mm, p=0.001). Those with cardiovascular disease showed no significant differences in true intra-arterial pathlength compared with young healthy volunteers (Right subtraction: YHV=431.6±50.1 mm, CVD=446.7±38.9 mm, p=0.094; Left subtraction:YHV=423.0±48.3 mm, CVD= 436.7±37.1 mm, p=0.129). These differences persisted on ANCOVA analysis, correcting for weight, blood pressure, BMI, and cholesterol levels. Conclusion: Increasing age results in a significant increase in the travelled pulsewave pathlength, however this difference is lost in those with atherosclerosis suggesting plaque has a cictrizing effect of the vasculature.